Sabdopalon Nayagenggong's Thesis: Historical, Philosophical, and Religious Education Studies - Iin Purnamasari; A.Y. Soegeng Ysh (Interdisciplinary Journal of Social Science and Education (IJSSE), 2024)
Abstract: This article aims to explore in depth the historical, philosophical, and educational aspects of Sabdopalon Nayagenggong's thesis. For this reason, this research is carried out through literature studies with a historiographic approach which includes heuristics, verification, interpretation, and historiography with a theoretical framework built based on thoughts in fibers, and historical books. Therefore, the research question of this study is how is Sabdopalon Nayagenggong's thesis from historical, philosophical, and religious education aspects. The findings of this study show that in the historical aspect, Sabdopalon Nayagenggong was an advisor to the last king of Majapahit Barwijaya V who was abandoned because he converted to Islam and who would restore Budi 500 years later. Jayabhaya called him Putra Betara Indra, Prabu Siliwangi called Budak Angon, Ranggawarsito called Satria Pinandhita Sinisihan Wahyu, among Balinese people known as Dang Hyang Nirartha/Mpu Dwijenndra Pedanda Sakti Wawu Rawuh/Tuan Semeru, in hinterland described as Semar; In the philosophical thesis, Sabdapalon (Semar) teaches Javanese concepts (kejawen), with its form or manifestation as 'among' kings / Javanese people as the conscience of every human being who comes from Allah / khalifatullah. In the thesis of religious education, it can be said that Sabdapalon-Nayagenggong has the characteristics of God, which is described as a divine reality with an abstract nature.